1991
DOI: 10.1161/01.atv.11.3.653
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipoprotein metabolism in normolipidemic men with and without coronary artery disease.

Abstract: A delayed clearance of postprandial lipoproteins from the plasma may play a role in the etiology of premature coronary atherosclerosis. To address this hypothesis, we studied chylomicron (remnant) metabolism in two groups of 20 selected normolipidemic men aged 35-65 years, a group of coronary artery disease (CAD) patients, and a matched control group with documented minimal coronary atherosclerosis. Subjects received an oral fat load supplemented with cholesterol and retinyl palmitate. Plasma samples obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
218
3
9

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 488 publications
(247 citation statements)
references
References 46 publications
17
218
3
9
Order By: Relevance
“…Patients with type III hyperlipoproteinaemia [8], chronic renal failure [40] or NIDDM [41] have elevated levels of remnant lipoproteins as well as accelerated development of atherosclerosis. Finally, elevated postprandial levels of triglycerides or remnant lipoproteins have also been found to be predictors of the presence, severity, progression or familial risk of atherosclerosis [42][43][44][45][46][47][48]. The present results therefore add to the growing evidence that remnant lipoproteins in the postprandial state may be involved directly in promoting atherosclerosis.…”
Section: U Rsupporting
confidence: 68%
“…Patients with type III hyperlipoproteinaemia [8], chronic renal failure [40] or NIDDM [41] have elevated levels of remnant lipoproteins as well as accelerated development of atherosclerosis. Finally, elevated postprandial levels of triglycerides or remnant lipoproteins have also been found to be predictors of the presence, severity, progression or familial risk of atherosclerosis [42][43][44][45][46][47][48]. The present results therefore add to the growing evidence that remnant lipoproteins in the postprandial state may be involved directly in promoting atherosclerosis.…”
Section: U Rsupporting
confidence: 68%
“…[Diabetologia (1994) proteins of intestinal origin were higher in patients with NIDDM [2]. In 1979 Zilversmit [3] suggested that triglyceride-rich lipoproteins of intestinal origin, especially the cholesteryl ester-rich chylomicron remnants, could play a very important role in atherogenesis, and since then, several reports have been published supporting this hypothesis [4][5][6][7][8][9][10]. Thus, our observation that postprandial lipaemia was increased in NIDDM raised the possibility that abnormalities in the metabolism of intestinally-derived lipoproteins may contribute to the increased risk of CHD in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the link between a high plasma triglyceride concentration and CHD is far from obvious. For example, patients with NIDDM and/or hypertriglyceridaemia have been shown to have increases in plasminogen activator inhibitor-1 [35,36], smaller, denser LDL particles [37,38], and increased postprandial lipaemia [2,39]; changes which have been proposed as increasing the risk of CHD in non-diabetic subjects [3][4][5][6][7][8][9]. It seems reasonable to speculate that a similar relationship between these changes and CHD would also exist in patients with NIDDM.…”
Section: Discussionmentioning
confidence: 99%
“…by a huge meta-analysis [5], as well as by intervention [6] and observational long-term [1] studies. In addition, postprandial hyperlipidaemia has been linked to atherosclerosis, even in fasting normocholesterolaemic subjects [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%